A multilevel study on the causal relationship in association network of work stress: Moderating effects of social support. Issue 4 (12th August 2019) - Yang, Fu-Chiang; Kao, Rui-Hsin; Cho, Cheng-Chung
Abstract : Purpose: The purpose of this paper is to examine the causal correlation between the work stress of immigration officers (IOs) and the cross-level effect of social support. Design/methodology/approach: A multilevel model was used to analyze the quantitative data obtained from 231 IOs in Taiwan, who served as the research objects. Findings: From the results of this study, it was found that a positive significant relationship existed between role conflict and work stress, as well as between work stress and job burnout. Also, cross-level context and moderating effect for the relationship between social support and work stress, as well as between social support, work stress and job burnout were obtained. Originality/value: This study only considered IOs in airports and ports. Therefore, it is necessary to determine if other topics of organizational behavior, such as the leadership of supervisors, organizational climate and work values of IOs, have a positive moderating effect. In this regard, it is recommended that a longitudinal study should be conducted in the future.